Development of innovative non-repeated annular area dual stage small-scale nitrogen axial turbine for hybrid open-closed Rankine cycle. (15th May 2018) - Khalil, Khalil M.; Mahmoud, S.; Al-Dadah, R.K.
Highlights: Novel non-repeated annual area dual stage axial turbine model has been studied. Using mean line and three dimensional simulations for turbine robust design method. Compare small axial turbine single stage with two stages repeated and non-repeated. Hybrid open-closed Rankine cycle thermal efficiency has been modelled and studied. Performance assessment for the three turbines configurations has been achieved. Abstract: This paper presents a novel, dual stage, small-scale nitrogen axial turbine with a non-repeated annular area for a hybrid, open-closed Rankine cycle. The proposed power cycle integrates a closed Rankine with an open Rankine power cycle using liquid nitrogen from a cryogenic energy storage system. In a small scale expander within the proposed cycle, there is a need for low flow rate and high expansion ratio to achieve higher cycle efficiency. These conditions make the choice and the design of a cycle turbine a challenging task, compounded with little experimental data accessible in the literature. Introduction of the increased annular area throughout the dual turbine passages will lead to reduced flow velocity and reduced flow losses thus improving the expander efficiency. This work contributes to the knowledge advancement in the development of small-scale nitrogen expander working in hybrid open-closed Rankine cycle by integrating the mean-line method with three-dimensional CFD simulation to develop three expander configurations single-stage, repeated two stages, and non-repeated two stages. The results revealed that the two-stage non-repeated annular area configuration manifested higher performance, with expander isentropic efficiency of 81.4% compared to 74.2% for the single stage configuration and 78.0% for the two repeated stage configuration at an expansion ratio of 3. Results also show that the thermal efficiency of the proposed cycle was increased by 5.7%.